Water Content and Specific Gravity of Pulai (Alstonia scholaris) Coppice Wood: Potential Utilization - Lies Indrayanti; Yanarita; Desy Natalia Koroh; Grace Siska; Herwin Joni; Mahdi Santosa; Yan Ciluk (Postgraduate, University of Mataram, 2026)
The study aims to determine the water content and specific gravity and analyze both on the potential utilization of pulai coppice wood. The study was conducted at the Forest Products Technology Laboratory, Forestry Department, Faculty of Agriculture, Palangkaraya University. Pulai coppice wood material was taken around the Palangka Raya University Campus, tree diameter 34cm, branch-free height 7m. Using a 2-factor factorial Randomized Block Design with 3 levels, the first factor is the axial direction, namely the base, middle and tip. The second factor is the radial direction, namely near the heart, between the heart and the bark and near the bark. The parameters observed were green water content, air-dry water content, green specific gravity, air-dry specific gravity and oven-dry specific gravity. The results showed an average value of green water content of 84.75%, air-dry water content of 18%, green specific gravity of 0.29%, air-dry specific gravity of 0.30% and oven-dry specific gravity of 0.31%. All parameter values ​​​​resulted from the research on pulai coppice wood were lower than the values ​​​​of the main stem pulai coppice wood from previous studies. In the axial direction, all parameter values ​​show an increasing pattern from base to tip, except for the wind-dry moisture content, which shows the opposite pattern. In the radial direction, the values ​​tend to be uniform, except for the green specific gravity, which decreases from the outside (near the bark) to the inside (near the heart). The results of the analysis of variance indicate that all parameters influence the axial direction, while only the green specific gravity influences the radial direction. This indicates that the axial factor dominates the physical properties of pulai coppice wood. The interaction factors that influence this are green water content and oven-dry specific gravity. Based on the specific gravity and wind-dry moisture content values, pulai coppice wood is lightweight and adapts quickly to its environment, thus quickly achieving dimensional stability. This pulai coppice wood is suitable for light construction and interior use.